O sentido ético da dramática de si e o significado político da poética da diferença na pragmática do ensino: considerações à luz de Foucault - Pagni, Pedro Ângelo [UNESP] (UPF Editora, 2014)
This essay discusses the theme of poetics in teaching activity, and discusses its possible ability to think about the ethical-formative sense and its possible political use to propose alternatives to the educational praxis that is restricted, in actuality, a pragmatic teaching. From the point of view of aesthetics of existence, therefore, we proposes a particular notion of poetic, fairly close to what can be understood by the dramatic that underlies the pragmatic of you last Foucault, as well as analyzes your chances to problematize the current pragmatic teaching. Thus, we look forward to assist the educator thinking both the possibility of ethics (self) transformation as the meaning of formation of another in his educational activity.

Este ensaio aborda a temática da poética na atividade docente e discute as suas possibilidades para se pensar o sentido ético-formativo e o seu eventual uso político para propor alternativas a uma práxis educativa que se restringe, na atualidade, a uma pragmática do ensino. Do ponto de vista da estética da existência, propõe, para tanto, uma particular noção de poética, bastante próxima ao que pode ser entendido pela dramática que subjaz à pragmática de si no último Foucault, assim como analisa suas possibilidades para que esta problematize a atual pragmática do ensino. Assim, vislumbra-se auxiliar o educador a pensar tanto a possibilidade ética de sua (auto)transformação quanto o sentido da formação do outro em sua atividade educativa.
The ethical sense of the dramatic of self and the political significance of poetics in teaching pragmatics: considerations in the light of Foucault
Keywords: Ética e Educação; Poética no ensino; pragmática de si; Foucault; Lyotard